Pengaruh Faktor Lingkungan pada Pembelajaran Jarak Jauh: Perbandingan antara Model Online dan Offline - Ageng Saepudin Kanda S; Yusti Maulidda (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research details an analysis of the impact of distractions on student resilience in the context of distance learning, with a focus on the comparison between online and offline models in the academic environment of the University of Digital Technology. The research method involves surveys and interviews to collect data on student perceptions of distractions, while observation is used to evaluate environmental factors that influence learning. The research results show that distractions have a significant role in determining the level of student resistance to distance learning. Environmental factors such as the availability of technological resources, social support, and a comfortable work space play an important role in reducing the impact of distractions. These findings provide a basis for developing strategies and policies that can improve student learning experiences in the context of online and offline learning in the digital era. The practical implications of the results of this research can help educational institutions to develop more effective guidelines for managing distractions and increasing student resilience.